The cognitive neuroscience of reading and dyslexia - Woollams, Anna (Henry Stewart Talks, 2010)
Why study reading?, Cognitive and neural components of reading, What is acquired dyslexia?, Attentional dyslexia, Neglect dyslexia, Hemianopic alexia, Pure alexia, Surface dyslexia, Phonological dyslexia, Deep dyslexia, Learning to read, Phonological awareness, Self-teaching, What is developmental dyslexia?, Semantic deficits, Developmental phonological dyslexia, Phonological deficits, Imaging evidence